Development of supplementary cementitious materials: a systematic review - Ali Mangi, Sajjad; Wan Ibrahim, Mohd Haziman; Hussain Khahro, Shabir; Jamaluddin, Norwati; Shahidan, Shahiron (Science & Engineering Research Support Society (SERSC), 2020)
Concrete is the essential development material utilized for common works and it is profoundly expensive. The interest in building materials, for example, concrete is becoming comprehensively because of the development in the populace. Around 3 billion tons of Portland concrete are at present devoured around the world, and around 400 kilograms of carbon dioxide (CO2) gas is discharged to deliver each 600 kilograms of concrete. As respects CO2 creation, its belongings are natural contamination. The presentation of Additional Cementitious Materials (SCMs) can finger it. SCMs practice is well known these days in view of its great accomplishment in the field of manageable development. Utilizing SCMs is a worthwhile movement for the development business, which gives minimal effort and earth neighborly development. SCMs have regularly been presented instead of Portland concrete, which builds solid quality and strength productivity. A great deal of work has been done on the utilization of SCMs in the assembling of green structure materials. This exploration article sums up the past outcomes concerning the utilization of SCMs as a fractional substitute for concrete. This paper will consequently give the kindred scientists, who are searching for extra cementitious materials in the field of solid assembling, with a noteworthy thought and helpful information.